Meso-pacing in Olympic and World Championship sprints and hurdles: Medallists save their best for the final - Hanley, B.; Hettinga, F. J. (Journal of Sports Sciences, 2021)
The aim of this novel study was to analyse performance changes across qualifying heats, semi-finals and finals in world-class sprinters and hurdlers. Finalists` finishing positions, times and rankings at the Olympic Games and IAAF World Championships (2012-2019) were obtained. 78% of gold, 67% of silver and 38% of bronze medallists won their qualifying heat and semi-final, and in most events final placings were associated with finishing positions in the qualifying heats (P <= 0.006), but not with finishing times. Medallists ran faster in each successive round (P < 0.001), whereas those finishing between 4th-6th did not improve on their semi-final times. Most athletes finishing last and second-last ran the final slower than both their semi-final and qualifying heats. The short hurdles events, with fixed barrier heights and distances, differed from the other races as the medallists were faster than most rivals in the qualifying rounds (P < 0.05), and their race times did not improve from the semi-final to the final. Coaches should note that the world`s best athletes were able to conserve energy for the final within a meso-pacing strategy throughout the championships, which was more important in the short hurdles, and requires preparation within their training regimens.